Papel de las familias en los procesos de educación inicial durante la pandemia COVID 19 en la Localidad de San Cristóbal - Bogotá - Rojas Sánchez, Shirley Paola (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This research work is related within the framework of the interest in determining the role that the family has played in the initial education processes, but under the environment of the health crisis produced by the COVID 19 pandemic in the town of San Cristóbal, city from Bogotá to 2022. This led to characterize the participation processes of the families of the kindergartens that it offers in early childhood care before and during the pandemic; is to describe the strengths and weaknesses in the process of family participation and; finally, identify the expectations of families in the educational process in these kindergartens. The problem on which the present study is framed is given by the worrying lack of participation of families in the teaching and learning processes in kindergartens of initial education. This situation poses new scenarios and challenges resulting from the current pandemic, given that it is a circumstance or phenomenon not foreseen by parents, nor by educational institutions and the State itself. As a consequence, the research question is set: what is the role of the family in the kindergartens offered by the initial education service in times of pandemic in the town of San Cristóbal-Bogotá by 2022? To respond to this concern, an investigation based on the qualitative approach and on a hermeneutical historical perspective was defined, in which the development of the grounded theory was vital, for which an interview was carried out, the development of a booklet for parents of family and the descriptive analysis product of the interviews. The main results focus on pointing out that the socioeconomic conditions of the town of San Cristóbal create barriers and make it impossible for parents to carry out processes of interrelation and co-responsibility with educational institutions. However, it is also evident that there is a significant number of families in which there is that level of co responsibility necessary to strengthen the comprehensive education of students.